Prevalence Estimation, Antimicrobial Susceptibility, and Serotyping of Salmonella enterica Recovered from New World Non-Human Primates (Platyrrhini), Feed, and Environmental Surfaces from Wildlife Centers in Costa Rica - Rojas Sánchez, Ernesto (2023)
Concern about zoonoses and wildlife has increased. Few studies described the role of wild mammals and environments in the epidemiology of Salmonella. Antimicrobial resistance is a growing problem associated with Salmonella that threatens global health, food security, the economy, and development in the 21st century. The aim of this study is to estimate the prevalence and identify antibiotic susceptibility profiles and serotypes of non-typhoidal Salmonella enterica recovered from non-human primate feces, feed offered, and surfaces in wildlife centers in Costa Rica. A total of 180 fecal samples, 133 environmental, and 43 feed samples from 10 wildlife centers were evaluated. We recovered Salmonella from 13.9% of feces samples, 11.3% of environmental, and 2.3% of feed samples. Non-susceptibility profiles included six isolates from feces (14.6%): four non-susceptible isolates (9.8%) to ciprofloxacin, one (2.4%) to nitrofurantoin, and one to both ciprofloxacin and nitrofurantoin (2.4%). Regarding the environmental samples, one profile was non-susceptible to ciprofloxacin (2.4%) and two to nitrofurantoin (4.8%). The serotypes identified included Typhimurium/I4,[5],12:i:-, S. Braenderup/Ohio, S. Newport, S. Anatum/Saintpaul, and S. Westhampton. The epidemiological surveillance of Salmonella and antimicrobial resistance can serve in the creation of strategies for the prevention of the disease and its dissemination throughout the One Health approach.